2022
DOI: 10.3233/shti210889
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Satisfaction and e-Learning Courses in Covid-19 Pandemic Era: A Case Study

Abstract: The present study is conducted to determine the status of e-learning, student satisfaction and the relationship between these two variables in Zahedan University of Medical Sciences (ZAUMS). According to a descriptive study, there was just a significant difference between the mean score of e-Learning experience and student satisfaction, and a positive correlation between the education level and student satisfaction. Also, there was a positive correlation between all variables of e-learning and student satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 8 publications
2
10
0
Order By: Relevance
“…Our study also showed that the standard of study materials, student-teacher communication, digital competences of the teacher and the student are positively correlated. This finding is in line with research [34], [35], which revealed a positive correlation between student-centred teaching design and the quality of distance education based on interactive communication methods and developed online communication. It can be concluded that the development of online learning applying user-friendly tools is an effective component of blended learning [35].…”
Section: Level Of Study Psupporting
confidence: 92%
See 1 more Smart Citation
“…Our study also showed that the standard of study materials, student-teacher communication, digital competences of the teacher and the student are positively correlated. This finding is in line with research [34], [35], which revealed a positive correlation between student-centred teaching design and the quality of distance education based on interactive communication methods and developed online communication. It can be concluded that the development of online learning applying user-friendly tools is an effective component of blended learning [35].…”
Section: Level Of Study Psupporting
confidence: 92%
“…This finding is in line with research [34], [35], which revealed a positive correlation between student-centred teaching design and the quality of distance education based on interactive communication methods and developed online communication. It can be concluded that the development of online learning applying user-friendly tools is an effective component of blended learning [35]. This is facilitated by digital infrastructure, support for student work and optimized, appropriately structured educational content in the form of study materials.…”
Section: Level Of Study Psupporting
confidence: 92%
“…Consumer satisfaction is important, and businesses must maintain it to survive and succeed in competition (Tj and Tanuraharjo, 2020 ). In recent years, satisfaction has been widely considered in e-learning (Erfannia et al, 2022 ; Ung et al, 2022 ). Satisfaction with an online course is a variable that involves a self-perceived range of fulfillment linked to the individual's wish to learn and is an indicator of a positive evaluation of a learning experience (Dal Santo et al, 2022 ).…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…Research has proved that course quality significantly contributes to consumer satisfaction (Li et al, 2012 ; Cheng, 2020 ). For example, Erfannia et al ( 2022 ) explained that better support of e-learning course quality resulted in more fabulous students' satisfaction at Zahedan University of Medical Sciences. Cheng ( 2020 ) indicated that course quality (content quality and design quality) positively contributed to students' satisfaction with the cloud-based e-learning system.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…n December 2019, a new coronavirus disease (COVID-19) outbreak appeared in Wuhan, China [1,2]. Due to fast transmission, COV-ID-19 was known as a pandemic in a few months worldwide, affecting public health, economic, and social conditions [3,4] with a wide range of clinical presentation and prognosis, such as the common cold, respiratory infections, multiple organ failure, and death [5,6].…”
mentioning
confidence: 99%